Effect of Addition of Clopidogrel to Aspirin on Stroke Incidence: Meta-Analysis of Randomized Trials. Issue 5 (July 2015) - Palacio, Santiago; Hart, Robert G.; Pearce, Lesly A.; Anderson, David C.; Sharma, Mukul; Birnbaum, Lee A.; Benavente, Oscar R.
Background: It remains controversial whether dual antiplatelet therapy reduces stroke more than aspirin alone. Aim: We aimed to assess the effects of adding clopidogrel to aspirin on the occurrence of stroke and major haemorrhage in patients with vascular disease. Methods: Meta-analysis of published randomized trials comparing the combination of clopidogrel and aspirin vs. aspirin alone that reported stroke and major bleeding. Results: Thirteen randomized trials were included with a total of 90 433 participants (mean age 63 years; 63% male) with a mean follow-up of 1·0 years and 2011 strokes. Stroke was reduced 19% by dual antiplatelet therapy (odds ratio = 0·81, 95% confidence interval 0·74–0·89) with no evidence of heterogeneity of effect across different trial populations (I 2 index = 5%, P = 0·4 for heterogeneity). Dual antiplatelet therapy reduced ischemic stroke by 23% (odds ratio = 0·77; 95% confidence interval 0·70–0·85); there was a nonsignificant 12% increase in intracerebral haemorrhage (odds ratio = 1·12, 95% confidence interval 0·86–1·46). Among 1930 participants with recent (<30 days) brain ischemia from four trials, stroke was reduced by 33% (odds ratio = 0·67, 95% confidence interval 0·46–0·97) by dual antiplatelet therapy vs. aspirin alone. The risk of major bleeding was increased by 40% (odds ratio = 1·40, 95% confidence interval 1·26–1·55) by dual antiplatelet therapy. Conclusions: This meta-analysis demonstrates a substantial relative risk reduction in stroke by clopidogrel plus aspirin vs. aspirin alone that is consistent across different trial cohorts. Major haemorrhage is increased by dual antiplatelet therapy.